Literacy Development in the Foundational Years of School: Teachers’ Experiences - Arya, Yatika; Joshi, Priti (Voices of Teachers and Teacher Educators, 2021)
Literacy skills develop over a period of time as young children interact with their environment in a variety of ways including the use of sounds and symbols. Literacy is a culturally valued and socially situated skill set developed in resourceful, responsive learning settings. This paper is an attempt to interpret the socio-cultural conceptualisation and practice of literacy by researching teachers’ lived experiences and understanding of literacy development in selected schools of Delhi.